2014
DOI: 10.1002/2014gl060332
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Dunedin whistlers using volcanic lightning

Abstract: Whistlers detected at Dunedin, New Zealand are an anomaly: there is little lightning around Dunedin's conjugate point yet whistlers appear in relatively large numbers. These surplus whistlers have consequently inspired investigations into their origins. Dunedin's lightning-sparse conjugate point lies in the Aleutian Islands, a region populated with active volcanoes. Their presence has allowed us to perform a novel analysis: the correlation of whistlers to volcanic lightning. We report on our investigation, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…In addition, the time of the daily peak of the whistler rate at Dunedin is in disagreement with the peak of lightning activity at the conjugate point (Rodger, Lichtenberger, et al, ). The results of Collier et al () suggest tropical Mexico, over 7,000 km from the conjugate point, as the source region, which, however, seem to contradict our understanding of the fundamental physics and also other observations (Antel et al, ; Morgan & Allcock, ).…”
Section: Introductionmentioning
confidence: 85%
“…In addition, the time of the daily peak of the whistler rate at Dunedin is in disagreement with the peak of lightning activity at the conjugate point (Rodger, Lichtenberger, et al, ). The results of Collier et al () suggest tropical Mexico, over 7,000 km from the conjugate point, as the source region, which, however, seem to contradict our understanding of the fundamental physics and also other observations (Antel et al, ; Morgan & Allcock, ).…”
Section: Introductionmentioning
confidence: 85%
“…Ezen kívül a whistlergyakoriság napi eloszlása is eltér a konjugált pont villámtevékenységének eloszlásától [Rodger et al, 2009b]. Collier et al [2010] szerint a konjugált ponttól több, mint 7000 kilométerre fekvő trópusi Mexikó a források helye, ez azonban ellentmond a terjedésről alkotott képünknek, valamint más megfigyeléseknek [Morgan & Allcock, 1956;Antel et al, 2014].…”
Section: Bevezetésunclassified
“…An impulsive current flowing in a lightning channel within a long ash plume can generate electromagnetic signals in the VLF range. It was found that electromagnetic signals originating in volcanic lightning discharges produced during the eruption of Mount Okmok volcano (Aleutian Islands) in 2008 traveled along the connecting magnetic field line to the opposite hemisphere and were recorded as whistlers at the conjugated point in Dunedin, New Zealand [Antel et al, 2014].…”
Section: Possibility Of Atmospheric Discharges On Marsmentioning
confidence: 99%